Ignoring Europe? Reassessing the British Labour Party’s Policy towards European Integration, 1951-60 - Matthew Broad (Nomos Verlagsgesellschaft mbH und Co. KG, 2022)
The 1950s were a turning point in British European policy during which the country moved from passive bystander to prospective member of the European Economic Community (EEC). Existing scholarship, though, depicts the opposition Labour Party as choosing largely to ignore this shift. This article by contrast shows that at various levels Labour did systematically talk about the vexed question of Britain’s European future. Indeed, a critical mass of the Party quickly recognised the necessity of a closer relationship with the EEC, supported membership of the Free Trade Area (FTA) as the best institutional forum for this undertaking and, following its collapse, sought with some energy to prevent the ensuing economic and political division of Western Europe. In revealing Labour policy as more nuanced and measured, the article aims ultimately to promote the 1950s as a far more crucial component in the broader story of how the Party grappled with closer cooperation among European states.